Type 2 diabetes presenting with DKA and severe hypertriglyceridaemia - Sim, Sing Yee; Marie-France, Kong; Faizanur, Rahman (Association of British Clinical Diabetologists, 2018)
Endolymphatic sac tumour (ELST) is a non‑metastasizing low grade adenocarcinoma of endolymphatic sac origin. It is also known as Heffner tumour, low grade adenocarcinoma of endolymphatic sac origin and aggressive papillary middle ear tumour. These tumours are closely associated with Von Hippel Lindau (VHL) disease. Here we report a case of Endolymphatic sac tumour in a 63 yr old lady who presented with left sided facial palsy. Since the tumour was highly vascular and required preoperative embolization, initial clinicoradiological diagnosis was Jugulotymphanic paraganglioma. Histopathology showed features of Endolymphatic sac tumour, which was confirmed by immunohistochemistry. Since this tumour is locally aggressive low grade adenocarcinoma, the diagnosis is difficult in advanced cases where there is erosion of petrous temporal bone or the lesion shows extension into cerebellopontine angle as in our case. Since the association of this tumour with VHL disease is well established, it is important to screen all the patients of VHL disease for this lesion and also all the patients of ELST should be screened for other lesions of VHL disease to aid in early diagnosis and treatment. The case is presented here for its rarity and difficulty in initial diagnosis.